A new course in physics Vol.I (FYBSc) - Bangui P.S., Phatak V.V., sardesai P.L., Patil C.G. and others (Sheth Pub, Mumbai, 2004)
Physics
ENGLISH
Keywords: A new course in physics Vol.I (FYBSc); Physics; Physics